Applied Homeopathy - Derbyshire, Martha (Homœopathic Links, 2015)
This article gives examples of how the basic principles of homeopathy occur throughout our lives, and also proposes that we can intentionally apply the lawofsimilars and that of infinitesimals in meditation, as healers and as practitioners of classichomeopathy.
Keywords: similars; infinitesimals; consciousness; mindfulness